Load Cell Design for Measurement of Propeller Thrust - Rosli, N A N; Wahid, M A; Othman, N; Zain, M Z Md; Ali, W K Wan (FTMD Institut Teknologi Bandung, 2024)
The design, analysis, and prototype testing of a load cell for measuring propeller thrust generated by propeller rotation in this study. Design concepts factors of safety, yield strength, stress, and strain values were evaluated using Solidworks simulation to ensure that the load cell would not fail. The force applied to the load cell is measured by four strain gauges connected in a Wheatstone bridge connection and amplified by HX711 amplifier. These instruments is then connected to Arduino and 16x2 LCD. A static testing was carried out to measure the thrust from an APC 6x4E propeller and compared with validated results to validate the accuracy of the load cell. The built-in load cell experimental results were compared to a commercialised load cell, manufacturer data and blade element momentum theory from other studies. A graph of thrust against propeller rotational speed was constructed. The rotational speed that starts to detect the thrust is about 2000RPM. The error between prototype load cell to the manufacturer, RC benchmark and BEMT is less than 1%, 0.05% and 0.05%, respectively.